Konstruksi Keadilan Gender Dalam Wacana dan Praktik Poligami - Kholisah, Nur; Jannah, Nurul (Jurnal Kajian Gender dan Anak, 2025)
This research is motivated by the structural inequalities and systematic impacts of polygamy in Indonesia, which often ignores the principle of gender justice. Although legally restricted by the Marriage Law and the Compilation of Islamic Law, requirements such as "wife's consent" and "guaranteed justice" are difficult to substantively implement due to strong patriarchal bias and unequal power relations. The purpose of this study is to analyze the construction of gender justice in the discourse and practice of polygamy through a multidisciplinary approach to uncover its psychosocial, economic, and health impacts. The research method used is descriptive qualitative analysis with theological, juridical, and sociological approaches, involving the reinterpretation of religious texts and an analysis of positive legal regulations in Indonesia. The results show that polygamy causes multidimensional suffering, including chronic subordination and anxiety for the first wife, the loss of full custody of children, and increased mental and physical health risks. Theologically, polygamy in the Qur'an is restrictive and contextual, not a universal recommendation. Therefore, monogamy is more aligned with the goals of Islamic marriage, namely sakinah (sacred, loving, and compassionate), while polygamy should be viewed only as a rukhsah (emergency relief) in very limited circumstances. Therefore, legal reconstruction based on gender equality is urgent to prevent exploitative practices.